Differences on Geochemical Characteristics and Their Implicating Significances of Nitrogen in Coal-Derived Gas and Oil-typed Gas in China - Xiaobo, Wang; Jian, Li; Chunxia, Yang; Zhisheng, Li; Jianfa, Chen; Yue, Zheng; Yifeng, Wang; Jin, Li; Chunlong, Yang; Aisheng, Hao; Shouguo, Ge (Frontiers in Earth Science, 2021)
Natural gases in China are main coal-derived gas and assisted with oil-typed gas. At present, many genetic identification methods from hydrocarbon composition and isotope, light hydrocarbon and biomarker indexes are formed, lacking of combining methods from non-hydrocarbon gases. Based on compositions and isotopes geochemical characteristics and their differences of non-hydrocarbon gas of nitrogen in coal-derived gas and oil-typed gas, and combing the isotopic geochemical characteristics of non-hydrocarbon of helium, the comprehensive identification methods of coal-derived gas and oil-typed gas for hydrocarbon gases according to the associated non-hydrocarbon gases of nitrogen and helium are established and the preliminary applications have been engaged. The main recognitions are as follow:（1）The coal-derived gas generally has relative lower nitrogen abundances mainly distributed from 0 to 31.2% with main frequency from 0 to 2%. While oil-typed gas usually has relative higher nitrogen abundances mainly distributed from 1.1% to 57.1% with main frequency from 2% to 16%. (2) The coal-derived gas generally has relative heavier nitrogen isotope values mainly distributed from -8‰ to 19.3‰ with main frequency from -8‰ to 8‰.While oil-typed gas usually has relative lower nitrogen isotope values mainly distributed from -10.6 ‰ to 4.6‰ with main frequency from -8‰ to 4‰.（3）The geochemical characteristics differences of coal-derived gas and oil-typed gas are mainly due to that the sapropel parent material is relative rich in nitrogen element and rich in light δ14N, while the humic parent material is relative poor in nitrogen element and rich in heavy δ15N, as well as the differences on thermal maturity of source rocks, the redox conditions of source rock sedimentary environment and the salinity of water body are also important effective factors.（4）Differences on nitrogen abundances and isotopes in coal-derived gas and oil-typed gas have great implicating significances in genetic identification. The genetic identification chart of R/Ra-δ15N for organic and inorganic nitrogen in natural gas and the comprehensive joint identification charts of R/Ra-δ15N-N2 of nitrogen and helium for coal-derived gas and oil-typed gas have been established, and have great important references in investigating the origins and sources of natural gas and guiding natural gas exploration in China.